Applications of Chapman-Richards model to geotechnical engineering - Nie, Wen (2020)
In this paper, the Chapman-Richards model is adapted to best fit three types of nonlinear curves that are generally encountered in geotechnical engineering practices, i.e. the degree of consolidation versus time factor curves in one-dimensional consolidation and plane strain consolidation under strip loading, the compressibility and permeability curves of soft clay, and the geometry parameters of geosynthetic tube versus pumping pressure curves. The methods of determining unknown parameters using the Chapman-Richards model are fully demonstrated. It is found that the Chapman-Richards model has its range of applications in geotechnical engineering and may provide unique insights into the complexity of geotechnical problems.